INTERPROFESSIONAL EDUCATION (IPE) IMPROVES STUDENTS' COMMUNICATION SKILLS: A LITERATURE REVIEW - Sri Sundari; Hadi Rai (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2021)
Background: Interprofessional education is a useful method for enhancing professional abilities in collaborative processes so as to create holistic health services. To improve collaboration skills, one of the competencies is the ability to communicate between professions. Therefore, it is necessary to know the existence of scientific evidence about the implementation of interprofessional education in improving student communication skills. Method: There was some original research which was published in the ProQuest and Google Scholar databases from 2013 to 2017. Results: There were 14 articles gotten from both inclusion and exclusion criteria. Articles collected using a quasi-experimental research design, and mix methods. Each article used a different implementation method to measure an increase in communication skills between students. Thirteen studies reported that students' communication skills increased, but there was one study that did not have a significance value for effective communication.Conclusion: Based on the research review, there are many intervention methods that can be used to improve student communication in the application of IPE. Thus, institutions can improve, manage learning strategies and implement IPE.